Evaluation of immunogenicity, efficacy and safety of GP40041 compared to Humulin® NPH in patients with type 2 diabetes mellitus - A. G. Zalevskaya; A. A. Mosikian; O. V. Afonkina; R. V. Drai (Izdatelstvo OKI, 2019)
Background. GP40041 is a biosimilar to Humulin® NPH. GP40041 is registered and administrated in Russia since 2004. However, due to changes in the regulatory requirements for biosimilar insulin development programme, we have conducted additional clinical trials of GP40041 including a comparative clinical trial of immunogenicity of biosimilar GP40041 and reference drug Humulin® NPH. Aims. To demonstrate a non-inferior immunogenicity, and comparable safety and effi cacy of GP40041compared to Humulin® NPH. Materials and methods. 201 patients with T2DM were recruited at 14 centers. We randomly assigned patients 1:1 to receive Humulin® NPH (98 patients, the active control group) or GP40041 (103 patients). The trial included 2 parallel groups of T2DM patients, who received insulin for 28 weeks: 4 weeks of titration period and 24 weeks of treatment period. The primary endpoint was the anti-insulin antibody concentration and its change at Week 12 and 24 as compared to baseline. The secondary endpoint was change in glycated hemoglobin (HbA1c) level, insulin daily dose and fasting plasma glucose (FPG) concentrations at Week 24 as compared to baseline. Results. There was no statistically signifi cant diff erence in terms of immunogenicity endpoints between GP40041 and Humulin® NPH groups. There was no diff erence in the change of HbA1c level and insulin dose aft er treatment between both groups. Both drugs were well tolerated. Adverse eff ects were comparable between treatment groups. All hypoglycemic episodes were light and the most of the episodes were registered during daytime. Frequency of hypoglycemic episodes was comparable between GP40041 and Humulin® NPH groups. Conclusions. GP40041 is comparable to Humulin® NPH in T2DM patients in terms of immunogenicity, safety and efficacy.